THE INFLUENCE OF SCIENTIFIC ATTITUDE, ACTIVE LEARNING, AND FRIENDLY CHARACTER ON SCIENCE LEARNING OUTCOMES IN JUNIOR HIGH SCHOOL STUDENTS - Ilhami, Mohamad; Amanah, Siti; Rahmawati, Sophia; Priyanto, Priyanto; Kumalasari, Ade; Kurniati, Erisa; Hayati, Suci; Nusantara, Duano Sapta (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This research investigates the combined influence of scientific attitude, active learning, and friendly character on the science learning outcomes of junior high school students in Kota Jambi. It explores how these factors contribute to student's academic performance and social development in science education. A mixed-methods approach was used, integrating quantitative data from questionnaires with qualitative insights from interviews. The sample consisted of junior high school students in Kota Jambi. Data analysis was performed using multiple regression tests with SPSS to examine the relationship between the variables. The results indicate that scientific attitude, active learning, and friendly character significantly and positively affect students' science learning outcomes. Active learning enhanced students’ engagement and critical thinking skills, while a strong scientific attitude improved their curiosity and problem-solving abilities. Students with well-developed, friendly character traits also demonstrated better social interactions, leading to more effective collaboration in group-based learning activities. Despite these positive outcomes, the study highlights the challenge of translating scientific concepts into real-world applications, which requires greater emphasis on contextual learning and motivation. This study offers a fresh perspective by integrating social-emotional traits such as friendly character into analyzing science learning outcomes, an area often overlooked in previous research. It provides actionable insights into how fostering active learning and positive social interactions can create a more engaging and effective science learning environment.